Advanced osteoradionecrosis of the maxilla: a 15-year, single-institution experience of surgical management. (1st December 2020) - Li, Zimeng; Liu, Shangping; Xie, Shang; Shan, Xiaofeng; Zhang, Lei; Cai, Zhigang
Abstract: Background: Osteoradionecrosis (ORN) of the maxilla is a rare disease. In contrast with a mandibular predominance, maxillary ORN has not been widely reported. Objective: To review clinical features, surgical treatments, and results of maxillary ORN and offer recommendations for surgical decision-making. Material and methods: We retrospectively reviewed medical records of maxillary ORN at our hospital between 2002 and 2017. Clinical data were collected, including age, sex, primary tumor characteristics, radiotherapy dose, clinical findings of maxillary ORN, and treatment outcomes. Descriptive statistics and multiple factors were analyzed. Results: Twenty-four patients were included for analysis. The primary symptoms of maxillary ORN were pain, trismus, pus, bone exposure, and skin fistula. Twenty (83.3%) patients were completely cured after single-operation. Thirteen patients underwent sequestrectomy, and the cure rate was 76.9% (10/13). Eleven patients received segmental osteotomy and flap reconstruction, with the cure rate of 90.9% (10/11). There was no significant statistical difference in the cure rate between these two groups ( p  = .596). Conclusions and significance: Compared with mandibular ORN, the surgical effect of maxillary lesions is better and the choice of operation methods can be relatively conservative. Both sequestrectomy and segmental osteotomy with flap reconstruction can achieve good results in appropriate conditions.